2014
DOI: 10.15407/spqeo17.02.155
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructures in lightly doped silicon carbide crystals with polytypic defects

Abstract: Abstract. In this work, photoluminescence spectra of lightly doped SiC crystals with ingrown original defects are reported. , N D  110 18 cm -3 were investigated. The analysis of absorption, excitation and low temperature photoluminescence spectra suggests formation of a new micro-phase during the growth process and appearance of the deep-level (DL) spectra. The complex spectra of the crystals can be decomposed into the so-called DL i (i = 1, 2, 3, 4) spectra. The appearance of the DL i spectrum is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Peculiarities of the Laue patterns of the D-layers in 6H-SiC crystals are the same as for the 3C-SiC crystals after phase transformation [9]. Pure samples with the SF-i and DL-i series, show a linear dependence of intensity of the DL-i spectra on the impurity concentration [9].…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Peculiarities of the Laue patterns of the D-layers in 6H-SiC crystals are the same as for the 3C-SiC crystals after phase transformation [9]. Pure samples with the SF-i and DL-i series, show a linear dependence of intensity of the DL-i spectra on the impurity concentration [9].…”
Section: Resultsmentioning
confidence: 64%
“…Pure samples with the SF-i and DL-i series, show a linear dependence of intensity of the DL-i spectra on the impurity concentration [9].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We studied low temperature spectra by using techniques described early [7]. For this experiment, we selected lumpy, blocky SiC crystals and crystals with steps of growth.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental results and theoretical calculations showed that the luminescence of different polytypes strongly influenced by defects [1][2][3]. The luminescence spectra [4,5] of SiC crystals and films with stacking faults (SF i ) in highpurity SiC [2] and with deep level (DL i ) [6][7][8][9] in lightly doped SiC reflect formation of intermediate metastable phases during 3C↔6H transitions. SF i and DL i spectra hand-in-hand follow the structure transformations.…”
Section: Introductionmentioning
confidence: 99%